Interior Chinatown [large type] - Yu, Charles, 1976- (Thorndike press large print Bill's bookshelf, 2020)
"Willis Wu doesn't perceive himself as a protagonist even in his own life: He's merely Generic Asian man. Sometimes he gets to be Background Oriental Making a Weird Face or even Disgraced Son, but he is always relegated to a prop. Yet every day he leaves his tiny room in a Chinatown SRO and enters the Golden Palace restaurant, where Black and White, a procedural cop show, is in perpetual production. He's a bit player here, too, but he dreams of being Kung Fu Guy--the most respected role that anyone who looks like him can attain. At least that's what he has been told, time and time again. Except by one person, his mother. Who says to him: Be more."--